(Im)parcialidade na comunicação jornalística : questões enunciativas e a subjetividade na linguagem - Euzebio, Valaci (2015)
This study discusses the existence (or not) of journalistic impartiality, given the existence of subjectivity in language, as widely discussed in academic circles, which explains this scientific reflection. The theme of the research focuses on the question of impartiality, which is perceived as one of the foundations of journalism, emphasizing that the very exemption on a theme already shows a positioning, and subjectivity being marked by the language used in the text. The justification shows that the media presents this diversity of relationships, making an analogy can be said that on one side is the speech for communication, and the other language of subjectivity, involving Communication Theory and the Theory of Enunciation. The corpus of analysis focuses on three news magazine Veja, the online format, published on its official site, involving the theme education, whose titles are In 2022, Brazil is a country of literate - and nothing else , Fies: application deadline for pre-selected ends on Tuesday , and Barriers to improve education in Brazil are political‟, says World Bank economist . This phenomenon involves language, language, man and society in a way that is impossible to separate them. They became inseparable. So, it is based on the need to investigate the impartiality and subjectivity in this genre: the online news. The methodology features a descriptive bibliography and with qualitative research approach. Accordingly, we developed a methodological path of reading and writing. The first chapter is introductory, presenting what will be addressed in this study. The second is aimed at Communication Theory: who does not communicate if trumbica; covering eight sections. The third chapter proposes a study of the Theory of Enunciation Benveniste: a look at the text; featuring six sections. The fourth is to methodology and analysis of the corpus; exposing seven sections, and the final considerations. Based on our theoretical and bibliographic input, we detected a detachment of the three news stories with journalistic impartiality, while we witness an approach to subjectivity in language